EFFECT OF DIFFERENT CRYOPROTECTANTS ON SPERM PLASMA MEMBRANE INTEGRITY OF OSMANABADI AND SIROHI BUCK SEMEN - DAGLI, N R; BAKSHI , S A; GULAWANE , S U; VANAGE , G (The Indian Journal of Animal Reproduction, 2023)
Semen was collected from six Osmanabadi and six Sirohi bucks weekly for six weeks by Artificial Vaginamethod. Semen was diluted using Tris Egg yolk Glycerol (TYG), Tris Egg yolk Ethylene Glycol (TYE) and Tris-Dimethyl sulphoxide (DMSO) dilutors (TYO) and evaluated for sperm plasma membrane integrity by HOS testat pre (S°C) and post freezing (-196°C at 24 and 72 hours) stage. At pre freezing (S°C) stage in Osmanabadibuck semen there was no significant difference (P>0.0S) across different dilutors with respect to HOS positivesperm percentage but in Sirohi bucks significantly higher sperm plasma membrane integrity was observed inTYO and TYG than TYE diluter. At 24 hours post freezing stage in Osmanabadi buck semen significantly higherplasma membrane integrity was noted in TYO than TYG am.I TYE dilutors. In Sirohi buck ::;ernen significantlyhigher plasma membrane integrity was noted in TYO than TYE diluter, TYG being intermediate. At 72 hrs postfreezing stage in Osmanabadi bucks semen there was no significant difference (p>0.0S) across different dilutorswith respect to HOS positive sperm percentage. In Sirohi bucks semen significantly, higher (P
Keywords: Osmanabadi semen; Sirohi semen; Cryoprotectants; Plasma membrane integrity; Buck frozen semen